A new application of acetylation for analysis of acidic heteropolysaccharides by liquid chromatography-electrospray mass spectrometry. (1st October 2020) - Li, Ye; Liang, Jun; Shen, Yu; Kuang, Hai-Xue; Xia, Yong-Gang
Highlights: UHPLC-ESI-MS was applied for analysis of polysaccharides by acetylation. A quantitative analysis of multi-monosaccharaides by single marker was proposed. An analytical workflow was developed for UHPLC-ESI-MS and QAMS. Abstract: A novel ultra-high-performance liquid chromatography-electrospray mass spectrometry (UHPLC-ESI-MS) method was proposed for simultaneous determination of neutral and acidic monosaccharaides by employing acetylation derivatization that is specialized for gas chromatography-mass spectrometry (GC-MS) analyses. The UHPLC-ESI-MS was carried out in a positive ionization mode with selective ion monitoring (SIM) of sodium adducts at m/z 385 (Ara, Xyl and Rib), 399 (Rha and Fuc), 443 (Glc, Gal and Man) and 457 (GlcA and GalA). The separation was achieved on a Cortecs C18 + (2.1 mm × 150 mm, 1.6 μm) within 8 min using acetonitrile water as the mobile phase without additional buffer salt added. Furthermore, quantitative analysis of the multi-monosaccharaides by single marker (QAMS) was developed and validated using a relative correction factor. The UHPLC-ESI-MS and QAMS were compared and successfully applied to analyze the monosaccharide contents of a purified acidic heteropolysaccharide previously isolated from Ephedra sinica . The established UHPLC-ESI-MS and QAMS approach possesses high precision, stability and repeatability, and can be widely used for high-throughput analysis of the monosaccharide compositions of plant polysaccharides.